Tapering: performance improvements as a result of reduced workloads
Groups of swimmers were compared using different tapers. One group tapered for four weeks, reducing the volume each week by 33%. The other abruptly reduced volume by 80% and stayed at that level for two weeks. Implications: It does not seem to matter if a taper is programmed gradually or instituted in an abrupt manner. 1. The major performance enhancement effect appears to come from the extra recovery that is facilitated when the volume of work is reduced by at least 60%. 2. Swimming intensity must be maintained to preserve functional power. 3. Pretaper training volume will affect the level of final performance more than will different taper programs. 4. Until further studies are completed it is best to set the upper limit for taper duration as four weeks.